DAMPAK RATE OF RETURN, INVESTOR TRUST, FUND LONGEVITY TERHADAP KINERJA REKSA DANA DENGAN MODERASI ASSET UNDER MANAGEMENT - Ali Rambe, Rois Mahbub; Ahmar, Nurmala; Sailendra (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Mutual fund is one of the investment instruments that are currently in great demand by many people. Determining a good mutual fund is inseparable from some personal assumptions, knowledge about mutual funds and the influence of information that is widely spread in the media. One of the aspects that investors can do before invest their funds in a mutual fund is to do a portfolio analysis of the mutual fund performance. This study aims to analyze the effect of the variable rate of return, investor trust, fund longevity and moderated by asset under management variables on the mutual fund performance. The period of this research was carried out from 2019 to 2021. The data used is secondary data of 85 mutual funds obtained from company websites and the Otoritas Jasa Keuangan website. Methods of data analysis using descriptive analysis and analysis with the SEM-PLS (Structural Equation Modeling-Partial Least Square) method. The results of this study indicate that the variable rate of return, investor trust, and fund longevity have a positive effect on mutual fund performance. The role of asset under management is proven to be able to moderate the influence of investor trust and fund longevity variables on mutual fund performance. However, the role of asset under management is not proven to be able to moderate the effect of the variable rate of return on the mutual fund performance.